Pengembangan Media Pembelajaran Dasar Listrik Elektronika Berbasis Prezi - Adinda Arani; Dwiprima Elvanny Myori (Jurnal Pendidikan Teknik Elektro, 2020)
This research is motivated by the limited use of instructional media which leads students to understand more easily in the learning process because the teacher focuses more on understanding concepts that tend to be abstract. The minimal use of instructional media in the learning process causes a lack of attention and a lack of understanding of students in the teaching and learning process so that many students seem unfocused and carry out other activities in carrying out learning. Therefore it is necessary to develop Prezi learning media designed to help students in more active learning. This study aims to produce valid and practical Prezi learning media. This study a research and development method with the 4D Model which is divided into the stages of define, design, develop, and disseminate. The subjects of this research were class X TITL SMK Muhammadiyah 1 Padang students who were registered in the first semester of the 2020/2021 school year. Based on the research result, the validity of the media is 89% with the valid category. Practicality test with teacher respondents with an average score of 86% of students an average of 84% stated that Prezi’s learning media was very practical. It is concluded that Prezi learning media is valid and practical to use in the teaching and learning process for Basic Electrical Electronic.